High intrapatient variability of tacrolimus exposure associated with poorer outcomes in liver transplantation. Issue 6 (19th April 2022) - Dopazo, Cristina; Bilbao, Itxarone; García, Sonia; Gómez‐Gavara, Concepción; Caralt, Mireia; Campos‐Varela, Isabel; Castells, Lluis; Hidalgo, Ernest; Moreso, Francisco; Montoro, Bruno; Charco, Ramón
Abstract: Tacrolimus (TAC) is a dose‐dependent immunosuppressor with considerable intrapatient variability (IPV) in its pharmacokinetics. The aim of this work is to ascertain the association between TAC IPV at 6 months after liver transplantation (LT) and patient outcome. This single‐center cohort study retrospectively analyzed adult patients who underwent transplantation from 2015 to 2019 who survived the first 6 months with a functioning graft. The primary end point was the patient's probability of death and the secondary outcome was the loss of renal function between month 6 and the last follow‐up. TAC IPV was estimated by calculating the coefficient of variation (CV) of the dose‐corrected concentration (C0 /D) between the third and sixth months post‐LT. Of the 140 patients who underwent LT included in the study, the low‐variability group (C0 /D CV < 27%) comprised 105 patients and the high‐variability group (C0 /D CV ≥ 27%) 35 patients. One‐, 3‐, and 5‐year patient survival rates were 100%, 82%, and 72% in the high‐variability group versus 100%, 97%, and 93% in the low‐variability group, respectively ( p = 0.005). Moreover, significant impaired renal function was observed in the high‐variability group at 1 year (69 ± 16 ml/min/1.73 m 2 vs. 78 ± 16 ml/min/1.73 m 2, p = 0.004) and at 2 years post‐LT (69 ± 17 ml/min/1.73 m 2 vs. 77 ± 15 ml/min/1.73 m 2, p = 0.03). High C0 /D CV 3–6 months remained independently associated with worse survival (hazard ratio = 3.57, 95% CI = 1.32–9.67, p = 0.012) and loss of renal function (odds ratio = 3.47, 95% CI = 1.30–9.20, p = 0.01). Therefore, high IPV between the third and sixth months appears to be an early and independent predictor of patients with poorer liver transplant outcomes.